Pendekatan Inovatif Dalam Pengembangan Kompetensi Kepelatihan Di Era Digital - Manalu, Nimrot; Avicenna Nst, Ilham Luthfi; Putra, Rizky Pratama; Perdana Saragih, Sonindo Manja; Lubis, Siti Aisyah (widya balina, 2024)
ABSTRACT In the digital era, technological advancements have transformed the coaching landscape, requiring coaches to develop more adaptive and innovative skills. This research discusses various innovative approaches that can be used to enhance coaches' competencies, particularly through the utilization of technologies such as artificial intelligence (AI), big data, and e-learning platforms. The focus of this research is on how technology can enhance training effectiveness, program personalization, and better communication between coaches and athletes. Although technology offers many benefits, this research also highlights the challenges faced, including issues of digital literacy and the balance between personal interaction and the use of digital tools. With the wise adoption of technology, coaches can enhance training quality and optimize athlete performance amidst the increasingly complex changes in the sports environment. ABSTRAK Di era digital, perkembangan teknologi telah mengubah lanskap kepelatihan, menuntut pelatih untuk mengembangkan keterampilan yang lebih adaptif dan inovatif. Penelitian ini membahas berbagai pendekatan inovatif yang dapat digunakan untuk meningkatkan kompetensi pelatih, terutama melalui pemanfaatan teknologi seperti kecerdasan buatan (AI), big data, dan platform e-learning. Fokus penelitian ini adalah bagaimana teknologi dapat meningkatkan efektivitas pelatihan, personalisasi program, serta komunikasi yang lebih baik antara pelatih dan atlet. Meskipun teknologi menawarkan banyak manfaat, penelitian ini juga menyoroti tantangan yang dihadapi, termasuk masalah literasi digital dan keseimbangan antara interaksi personal dengan penggunaan alat digital. Dengan adopsi teknologi yang bijaksana, pelatih dapat meningkatkan kualitas pelatihan dan mengoptimalkan performa atlet di tengah perubahan lingkungan olahraga yang semakin kompleks.